248 The detrimental effect of pregnancy-associated bile acid homeostasis disorder on fetal pig death. (7th December 2018) - Fang, Z; Zhong, H; Yuan, P; Lin, S; Zhang, X; Li, J; Che, L; Feng, B; Lin, Y; Xu, S; Wu, D; Burrin, D
Abstract: The objective of this study was to determine bile acid metabolism and its association with fetal pig death in pregnant gilts. A total of 430 gilts/sows with similar genetic background (Landrace×Yorkshire) were included in this study, 407 of them from parity 1 to 9 were selected to evaluate the critical time of fetal death, 12 gilts implanted with cephalic vein catheters were used to determine the relationship of bile acid metabolism with fetal death, and additional 11 pregnant gilts at gestation day 60 (G60) and 90 (G90), respectively, were sacrificed at 8h postprandial for determination of mechanism accounting for disrupted bile acid homeostasis and fetal death. Pregnant gilts had raised serum total bile acids (TBA), which reached peak levels (7.10–67.00 μmol/L) at G90, and was 1–8 time that at G60 (4.10–20.00 μmol/L). Moreover, fetal death predominantly occurred during late pregnancy, with 70.67% of dead fetuses observed from G76 to farrowing. Fetal mortality was positively correlated with the increasing of TBA ratio of G90/G60, and significant difference in fetal survival appeared between the ratio "<6" and "≥6" gilts (7.6% vs 28.6%, P<0.05). Further analysis showed that repressed farnesoid X receptor (FXR) activity (P<0.05), probably induced by sulfated progesterone metabolites, was the triggering factor causing increased bile acid synthesis, but not the final decision maker of cholestasis, which depended on the balance of hepatic bile acid synthesis and sulfation capacity. Importantly, the increased expression of SLC27A5 (P<0.001) and unparallel expression of hepatic sulfotransferase 2A1 (SULT2A1) and cytochrome P450 7A1 (CYP7A1) in fetal liver inevitably led to accumulation of the risk bile acids, taurine-conjugated bile acid (T-CBA), in developing fetuses, increasing the risk of fetal demise. Conclusion: Our results show that bile acid homeostasis is disrupted in pregnant gilts, and fetal pig death is highly correlated with maternal bile acid homeostasis.